Hunting: Spear Flight Profiles - Hurkett, Cheryl (Journal of Interdisciplinary Science Topics, 2017)
We build upon our previous work on prehistoric spear velocity and use Excel to calculate the velocity throughout the spear’s motion and therefore calculate the maximum range it could achieve with and without a launching aid such as an atlatl.